HvPap-1 C1A Protease Participates Differentially in the Barley Response to a Pathogen and an Herbivore - Diaz-Mendoza, Mercedes; Velasco-Arroyo, Blanca; Santamaria, M. Estrella; Diaz, Isabel; Martinez, Manuel (Frontiers in Plant Science, 2017)
Co-evolutionary processes in plant-pathogen/herbivore systems indicate that protease inhibitors have a particular value in biotic interactions. However, little is known about the defensive role of their targets, the plant proteases. C1A cysteine proteases are the most abundant enzymes responsible for the proteolytic activity during different processes like germination, development and senescence in plants. To identify and characterize C1A cysteine proteases of barley with a potential role in defense, mRNA and protein expression patterns were analyzed in response to biotics stresses. A barley cysteine protease, HvPap-1, previously related to abiotic stresses and grain germination, was particularly induced by flagellin or chitosan elicitation, and biotic stresses such as the phytopathogenic fungus Magnaporthe oryzae or the phytophagous mite Tetranychus urticae. To elucidate the in vivo participation of this enzyme in defense, transformed barley plants overexpressing or silencing HvPap-1 encoding gene were subjected to M. oryzae infection or T. urticae infestation. Whereas overexpressing plants were less susceptible to the fungus than silencing plants, the opposite behavior occurred to the mite. This unexpected result highlights the complexity of the regulatory events leading to the response to a particular biotic stress.